Operationalizing Intersectionality: an Approach to Uncovering the Complexity of the Migrant Job Search in Australia. Issue 4 (20th February 2017) - Ressia, Susan; Strachan, Glenda; Bailey, Janis
Abstract : This paper explores the complexities surrounding the lived experiences of skilled migrant women and men from non‐English speaking backgrounds (NESBs) who arrive in Australia and attempt to seek work. The paper will analyze the migrants' experiences using intersectionality theory as a framework. Drawing on Anthias's social relations framework, this research will contribute to the field by demonstrating how intersectionality theory can be operationalized to understand the complex lived experiences of disadvantaged groups. The research will reveal how being a new migrant in Australia, unfamiliar with local job search processes, complicates jobseeking. The paper will show how gender and family roles impact this process, especially when young families are involved. Both genders suffer downward occupational mobility, with men seeking any type of work to get by, and women gravitating towards insecure forms of employment, or exiting the labour force, in order to manage the family unit.